Post-award grant collaboration: facilitators and hindrances to cross-disciplinary authorship - Basore, Chelsea; Mohammed, Susan; Tirrell, Bruce; Marhefka, Jacqueline; Hamilton, Katherine; Zhang, Tianyi; Davis, Carri; Hong, Howard; Liao, Xueyi; Miller, Grace (Frontiers in Education, 2025)
Granting agencies often require cross-disciplinary team composition to be competitive for funding. However, to what extent do research teams have cross-disciplinary authorships after they win an award, given that grants are not contracts? This mixed-method study examined the degree to which cross-disciplinary composition translated into cross-disciplinary authorship in grant-funded teams and the factors motivating cross-disciplinary collaboration. We found that after receiving a grant award, nearly 90% of investigators chose to collaborate across disciplines, with 80% working with researchers from fields very different from their own. Interviews uncovered facilitators and hindrances to continued collaboration. Facilitators included strong interpersonal relationships, shared goals, and openness to new ideas. Common hindrances involved funding shortages and limited face-to-face interactions. What defined success in cross-disciplinary collaboration were not only research outputs but learning opportunities, highlighting the intangible benefits of cross-disciplinary research. Researchers stressed the importance of integration and resource availability for deeper collaboration across disciplines.